Vontimitta Temple as an Architectural Masterpiece of the Kadapa, Andhra Pradesh: A Study (International Journal of Fine, Performing and Visual Arts, ISSN: 3006-6581, 2025)
This research study enhances the great observation and great analysis in, which is a sacred place. Vontimitta, situated in the Kadapa area, Andhra Pradesh, stands like a great antiquity and remarkable site of finest (oldest) and architectural significance that was mainly centered the Sri Kodandarama Swamy Temple.